The Literary Motif of the Exposed Child (cf. Ex. II 1-10) - Redford, Donald В.
u. a. Ḫurritisch, cf. J. Friedrich, ZA NF 15 (1950) 225-234; Semiramis, cf. Diodorus, Bibl. II 9; Sargon, cf. H. G. Güterbock, ZA 42, 62 ff.; Humai; Gilgameš, nach Aelian, Hist, animal. XII 21; Kyros, nach Herodot I 108 ff.